Mice lacking Bmp6 function. - Solloway, M; Dudley, A; Bikoff, E; Lyons, K; Hogan, B; Robertson, E (1998)
Bmp6, a member of the 60A subgroup of bone morphogenetic proteins (BMPs), is expressed in diverse sites in the developing mouse embryo from preimplantation stages onwards. To evaluate roles for Bmp6 signaling in vivo, gene targeting was used to generate a null mutation at the Bmp6 locus. The resulting Bmp6 mutant mice are viable and fertile, and show no overt defects in tissues known to express Bmp6 mRNA. The skeletal elements of newborn and adult mutants are indistinguishable from wild-type. However, careful examination of skeletogenesis in late gestation embryos reveals a consistent delay in ossification strictly confined to the developing sternum. In situ hybridization studies in the developing long bones and sternum show that other BMP family members are expressed in overlapping domains. In particular we find that Bmp2 and Bmp6 are coexpressed in hypertrophic cartilage, suggesting that Bmp2 may functionally compensate in Bmp6 null mice. The defects in sternum development in Bmp6 null mice are likely to be associated with a transient early expression of Bmp6 in the sternal bands, prior to ossification. These sternal defects are slightly exacerbated in Bmp5/6 double mutant animals.